Factors affecting theft and mutilation of library materials in the U.P. Diliman Main Library - Operario, Iris Marigold P. (1998)
The purpose of this study is to determine the factors affecting theft and mutilation of library materials and the possible preventive measures in lessening these library crimes as perceived by the library users and the librarians in the UP Diliman Main Library.